Segmentation of cell nuclei within complex configurations in images with colon sections - Rogojanu, Radu; Bises, Giovanna; Smochina, Cristian; Manta, Vasile (2010 IEEE International Conference on Intelligent Computer Communication and Processing, 2010)
This paper addresses the development of an automatic segmentation technique for detecting cell nuclei. The technique uses a new approach for segmenting nuclei in images taken from tissues with colon carcinoma. The segmentation problems encountered in these images and solved by the proposed technique are related to the non-uniform illumination on the background, out-of-focus nuclei, the physical structure of cells in the tissue section, the activity status of the cell and the clustered cell nuclei. First, the region growing method is used for accurate background detection. The separation regions between grouped cell nuclei are detected using the cross-correlation method and validated based on their link with the background. Then, the nuclei boundaries are identified by applying the watershed algorithm on the complemented distance transform of the binary image containing the selected separation lines.